New media coming to Kapkoi. (1st June 2019) - Gustafsson, Jessica
This article, by partly adopting a historical perspective, examines the introduction of new media in a Kenyan rural village, Kapkoi, and how it changes the communication ecology in the village. Further it explores how people in Kapkoi use and ascribe meaning to media. The article argues that categories such as gender, age and financial situation influence people's access to and use of media and demonstrates how media use can simultaneously reinforce and challenge power structures. Moreover, it highlights the clear digital divide between rural areas and urban centres, and yet suggests that the introduction of new media is partly owing to the connection between the urban and the rural and that media and communications technologies sustain and increase the connectedness of the local.